Peran Spiritualitas terhadap Kesiapan Mental sebelum Bertanding pada Student Athlete - Arief, Anisa; Akbar, Amin; Amin Akbar (Psikis : Jurnal Psikologi Islami, 2025)
Mental readiness is an essential psychological component that enables athletes to manage pressure and perform optimally in competitive situations. For student-athletes, these demands become more complex due to the dual responsibilities of academics and sports. Spirituality is believed to serve as an important psychological resource that helps reduce anxiety, regulate emotions and strengthen confidence before competition. This study aimed to explore how spiritual values shape student-athletes’ mental readiness and how they balance spiritual practices with academic and training demands. Using a qualitative descriptive design, data were collected through semi-structured interviews with nine student-athletes from various sports disciplines and analyzed using thematic analysis. The findings revealed four major themes: spiritual practice, inner peace, the meaning of competition and time management. Spirituality was found to function not only as religious worship but also as a psychological mechanism that supports emotional regulation, meaning-making and readiness to face competition. These results highlighted the importance of integrating spirituality into psychological training programs for student-athletes. It is recommended that future studies focus on developing and evaluating structured, spirituality-based interventions within varied athletic settings